In vitro Symbiosis of Reef-Building Coral Cells With Photosynthetic Dinoflagellates - Kawamura, Kaz; Sekida, Satoko; Nishitsuji, Koki; Shoguchi, Eiichi; Hisata, Kanako; Fujiwara, Shigeki; Satoh, Noriyuki (Frontiers in Marine Science, 2021)
Coral reefs are the biodiversity hot spots of the oceans, but have suffered from increasing environmental stresses caused principally by anthropogenic global warming. The keystone species of coral reefs are scleractinian corals, which maintain obligatory symbiotic relationships with photosynthetic dinoflagellates or zooxanthellae. Understanding cellular and molecular mechanisms of symbiosis is therefore essential for future preservation of coral reefs. To date, however, almost no single-cell level experimental systems have been devised to illuminate such mechanisms. To this end, our previous study established stable in vitro cell culture lines, including IVB5, originating from planula larvae of the stony coral, Acropora tenuis. Here, we show that soon after mixture with the zooxanthella, Breviolum minutum, flattened amorphous cells with endodermal properties exhibited elevated locomotor activity using filopodia and lamellipodia and interacted with zooxanthellae. Several minutes thereafter, coral cells began to endocytose B. minutum, and in vitro symbiosis was accomplished within 30 minutes. Nearly a half of the coral cells had incorporated algal cells within 24 hours in a reproducible manner. Coral cells that harbored zooxanthellae gradually became round and less mobile, and the zooxanthellae sometimes settled in vacuole-like structures in coral cell cytoplasm. This symbiotic state was maintained for at least a month. The IVB5 line of A. tenuis therefore provides an experimental system to explore cellular and molecular mechanisms involved in establishment of coral symbiosis at the single-cell level, results of which may be useful for future preservation of coral reefs.